Serum Resistin Level in Obese Male Children - Anis Amirhakimi; Hamdollah Karamifar; Hosein Moravej; Gholamhosein Amirhakimi (Journal of Obesity)
Objectives. Resistin is a member of cysteine-rich molecules. Several studies have been carried out to determine the biological effect of resistin, nevertheless a significant number are animal studies. All the studies performed regarding the relationship between serum resistin and obesity were merely accomplished in women. To the best of our knowledge, there is no survey on the correlation of the serum resistin level and obesity in male children. The aim of the present study is to assess serum concentration of resistin in obese male children. Methods. Between June 2009 and January 2010, we enrolled 42 randomly selected obese male students (body mass index (BMI) >95th percentile, age 15.7±1.5). Thirty-eight healthy age-matched male students with normal BMI (<85th percentile) were selected as a control group for the purpose of comparison of the serum resistin levels. Results. Serum resistin levels were measured in obese and control group. No significant difference was found between resistin levels of the 2 groups (obese: 9.21±5.6 ng/mL versus normal: 9.83±4.3 ng/mL; 𝑃=.582). There was no significant correlation between serum resistin level and BMI. Assessing the resistin level in male subjects was the distinct feature of our study. The outstanding finding of this research is that there is no correlation between serum resistin level and obesity. Conclusion. We have demonstrated that there is no correlation between obesity in male children and resistin level. Consequently, metabolic abnormalities of insulin resistance seen in obese male patients are not related to resistin.